2013
DOI: 10.3168/jds.2012-6260
|View full text |Cite
|
Sign up to set email alerts
|

Timed artificial insemination programs during the summer in lactating dairy cows: Comparison of the 5-d Cosynch protocol with an estrogen/progesterone-based protocol

Abstract: The objective of this study was to compare a GnRH-based to an estrogen/progesterone (E2/P4)-based protocol for estrous cycle synchronization and fixed timed artificial insemination (TAI), both designed for synchronization of ovulation and to reduce the period from follicular emergence until ovulation in cows with a synchronized follicular wave. A total of 1,190 lactating Holstein cows (primiparous: n=685 and multiparous: n=505) yielding 26.5 ± 0.30 kg of milk/d at 177 ± 5.02 d in milk were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 39 publications
9
50
3
6
Order By: Relevance
“…In this way, the association of estrus detection and FTAI protocols could be beneficial to improve pregnancy rates, as observed in our study. A greater number of heifers displaying estrus in the conventional (61.4%, 62/101) compared to J-Synch protocol (38.6%, 39/101, P= 0.003) was observed, in agreement with previous studies (Perry and Perry, 2008;Sa Filho et al, 2011a;Pereira et al, 2013). Administration of ECP can increase pre-ovulatory estradiol concentration, increasing the number of animals in estrus (Perry and Perry, 2008).…”
Section: Resultssupporting
confidence: 89%
“…In this way, the association of estrus detection and FTAI protocols could be beneficial to improve pregnancy rates, as observed in our study. A greater number of heifers displaying estrus in the conventional (61.4%, 62/101) compared to J-Synch protocol (38.6%, 39/101, P= 0.003) was observed, in agreement with previous studies (Perry and Perry, 2008;Sa Filho et al, 2011a;Pereira et al, 2013). Administration of ECP can increase pre-ovulatory estradiol concentration, increasing the number of animals in estrus (Perry and Perry, 2008).…”
Section: Resultssupporting
confidence: 89%
“…Therefore, proestrus and dominance length (Bleach et al, 2004;Cerri et al, 2009) cannot be ruled out as possible causes related to the reduced fertility observed. Increased length of proestrus (Ribeiro et al, 2012) and display of estrus at AI (Pereira et al, 2013) are associated with a reduction in pregnancy losses. Furthermore, Pereira et al (2014) reported that animals that display estrus at AI had decreased pregnancy losses regardless of the diameter of the preovulatory follicle.…”
mentioning
confidence: 97%
“…Comparisons of the use of EB (2 mg) vs. GnRH at the beginning of a FTAI program have reported variable results. For example, Pereira et al (2013a) compared the 5-days Cosynch protocol, a GnRH-based protocol, to an E2/P4 protocol in Holstein cattle (n = 1,190) during the summer. They reported better synchronization rate for the GnRH compared to the E2 protocol (78.2 vs. 70.7%; P = 0.02).…”
Section: Effectiveness Of Gnrh-based Protocols For Follicle Wave Emermentioning
confidence: 99%